2021
DOI: 10.1111/1462-2920.15444
|View full text |Cite
|
Sign up to set email alerts
|

The architecture of a mixed fungal–bacterial biofilm is modulated by quorum‐sensing signals

Abstract: Summary Interkingdom communication is of particular relevance in polymicrobial biofilms. In this work, the ability of the fungus Ophiostoma piceae to form biofilms individually and in consortium with the bacterium Pseudomonas putida, as well as the effect of fungal and bacterial signal molecules on the architecture of the biofilms was evaluated. Pseudomonas putida KT2440 is able to form biofilms through the secretion of exopolysaccharides and two large extracellular adhesion proteins, LapA and LapF. It has two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…Firstly, bacterium–fungus combinations were tested in liquid medium: GPP (Glucose-Proline-Phosphate) minimal medium [ 21 ], Czapek’s Dox [ 29 ], CDM (chemical defined medium) [ 30 ] and plantarum minimal medium (PMM5) [ 27 ], all with glucose as a carbon source. In subsequent experiments, we used MRS broth (Condalab) with glucose as a control medium and MRS broth without dextrose and beef extract (Condalab) with 1% ( w / v ) starch as the carbon source.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, bacterium–fungus combinations were tested in liquid medium: GPP (Glucose-Proline-Phosphate) minimal medium [ 21 ], Czapek’s Dox [ 29 ], CDM (chemical defined medium) [ 30 ] and plantarum minimal medium (PMM5) [ 27 ], all with glucose as a carbon source. In subsequent experiments, we used MRS broth (Condalab) with glucose as a control medium and MRS broth without dextrose and beef extract (Condalab) with 1% ( w / v ) starch as the carbon source.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been shown that some Gram-positive organisms such as Lactobacillus plantarum also respond to these molecules [ 19 ]. Furthermore, farnesol (a terpene) and dodecanol (an alcohol) induce different responses among fungi [ 20 ] and affect biofilm formation differently in consortia of Ophiostoma piceae and Pseudomonas putida [ 21 ]. Biofilms allow microorganisms to adhere and form a resistant new ecological niche [ 22 ]; the regulation of biofilm formation by QS in bacteria and fungi has already been demonstrated [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cross-talk) with the synthetic Esa QS circuit. It has been previously described that P. putida KT2440 does not produce any of the common signal molecules typically involved in QS systems described in other bacteria (Fernández-Piñar et al, 2011;Ruiz et al, 2021;Subramoni and Venturi, 2009). The genome of this strain appears to display a single open reading frame (PP_4647) that encodes an unpaired transcriptional regulator belonging to the LuxR protein family-i.e.…”
Section: The P Esas Promoter Exerts a Differential Transcriptional Re...mentioning
confidence: 96%
“…Very few studies currently look at inter-kingdom communication [20]. However, as we learn more about fungal communication systems we can envision to see more studies programming population level behaviours in yeast and fungi as well as in inter-kingdom contexts [21,22,23,24,25].…”
mentioning
confidence: 99%